Cure dialitiche domiciliari. Una frontiera da raggiungere, senza trascurare le criticità - Giuseppe Vanacore; Antonio Santoro (AboutScience Srl, 2020)
The National Plan of Chronicity, approved by the Italian State-Regions Conference, refers to the topic of home care, specifying how the fundamental objective of chronic care systems is to keep the sick person at home as much as possible. Currently, home dialysis - both peritoneal and haemodialysis - uses high-quality safe technology systems and allows patients to perform therapy safely at home. ANED wishes to stress that the choice of dialysis treatment, which certainly depends on clinical evaluations, must at the same time consider the psychological and emotional aspects of the patient, the expectations and needs of his life and the social context, aiming at an increasingly personalized and sustainable therapy for patients and the healthcare system.